Development of Contextually-Based Animated Video Media for Improving Speaking Abilities in Children with Speech Delay - Trimartini, Trimartini; Sukinah, Sukinah (Journal of Innovation and Research in Primary Education, 2025)
Speech delay affects 3-15% of school-age children, requiring innovative interventions that combine engaging multimedia elements with evidence-based pedagogical approaches. Traditional therapeutic methods often lack the multimodal stimulation necessary to maintain attention and motivation in young children with speech delay. This study aimed to develop and evaluate the effectiveness of contextually-based animated video media for improving speaking abilities in children with speech delay using the ADDIE development model. A research and development methodology employed the ADDIE framework with single-subject experimental design. One 4-year-old child with diagnosed speech delay participated as the primary subject. Data collection utilized expert validation scales for media and content assessment, systematic observation protocols for speaking ability measurement, and teacher response questionnaires. Expert validation involved content and media specialists evaluating technical quality and educational appropriateness. Speaking ability was assessed across five indicators using 5-point rating scales, comparing performance between traditional image media and animated video media conditions. Expert validation confirmed high feasibility with media quality scoring 4.3/5.0 and content appropriateness 4.2/5.0. Teacher evaluation demonstrated exceptional reception at 95.8%. Comparative assessment revealed 16% improvement in overall speaking ability when using animated video media versus traditional image media, with enhancements observed in articulation clarity, word production, and verbal responsiveness across four of five assessed indicators. Contextually-based animated video media proved feasible and effective for improving speaking abilities in children with speech delay. The integration of multimedia learning theory with contextual learning principles offers promising directions for technology-enhanced speech interventions, though larger-scale randomized controlled trials are needed to establish robust evidence for clinical practice.